Power in a minor key: Rethinking anthropological accounts of power alongside London's community organisers. (September 2021) - Samanani, Farhan
Anthropological accounts of power remain characterized by an enduring tension. Social scientific theories of power allow anthropologists to situate subjects and mediate between contending perspectives. However, in doing so, such theories inevitably also end up displacing the grounded perspective of interlocutors themselves. This tension sustains a contentious debate, which positions attention to power and attention to grounded perspectives in opposition. In this article I draw on ethnography conducted with the UK's largest community organising body, Citizens UK, to trace an alternative approach to this tension. For Citizens UK organisers this tension becomes a way of driving change by enrolling diverse actors in collective projects and by displacing hegemonic understandings from within. Good theories, for Citizens UK organisers, are characterised by the practical ability to mediate between contending positions and, in doing so, transform them. To make sense of this mode of theorisation I take up queer theorist Jack Halberstam's notion of 'low theory', geographer Cindi Katz's notion of 'minor theory', and I draw on the linguistic anthropology notion of 'register'. This allows me to unpack how organisers use theory to act, but also to trouble established anthropological understandings of what theory is and what it ought to do.